Tailoring the room temperature ferromagnetism in TiO2 nanoparticles by modulating the concentration of surface oxygen vacancy via La incorporating. Issue 10 (July 2019) - Zhang, Hong; Wang, Yuzhu; Zhong, Weijie; Long, Bo; Wu, Yibing; Xie, Zhi
Abstract: La-incorporated TiO2 nanoparticles (Ti1- x La x O2 ) were synthesized by a sol-gel method followed by vacuum annealing at 500 °C for 4 h, and were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), Raman scattering spectroscopy, and vibrating sample magnetometer (VSM), respectively. The results indicated that La ions were incorporated with TiO2 without distorting the tetragonal anatase structure, and a small amount of La ions were doped into TiO2 lattice by substituting the surface Ti sites, whereas most of the La atoms evenly distribute into TiO2 matrix in the form of La2 O3 . The incorporation of La ions with TiO2 matrix modulates the concentration of surface oxygen vacancy in Ti1- x La x O2 nanoparticles. The room temperature ferromagnetism (RTFM) in Ti1- x La x O2 nanoparticles varies with the concentration of surface oxygen vacancy due to ferromagnetic coupling interactions between singly ionized oxygen vacancy, thus RTFM can be tailored by modulating the concentration of surface oxygen vacancy via La ions incorporating.